Die pastorale Situation der Kirche Spaniens und das Axiom "sentire cum ecclesia" - Molina, Diego M. (Trierer theologische Zeitschrift, 2012)
" In his guest lecture at the Theological Faculty of Trier the pastoral theologican of Granada explqains the situation an the challenges, the opportunities und current tasks of the Catholic church of Spain in the post-Franco era. His critical am constructive analysis follows consistently the Ignatian motto "sentire cum ecclesia"